Treatment of IgG4-Related Disease - Kawano, Mitsuhiro; Yamada, Kazunori (Current Immunology Reviews (Discontinued), 2011)
Corticosteroids are commonly used to treat autoimmune pancreatitis (AIP) and IgG4-related disease other than AIP, and a dramatic response is expected. Although spontaneous improvement is sometimes observed, steroid therapy is useful to relieve the clinical features including obstructive jaundice and abdominal pain. Deteriorated endocrine and exocrine pancreatic function is also a target of treatment. Due to the relatively high recurrence rate of IgG4-related disease, maintenance therapy with low dose corticosteroids or combination therapy with corticosteroid and immunosuppressive drugs including azathioprine, mycophenolate, or 6-mercaptopurine is sometimes required. However, there is no consensus about when to stop steroid therapy, the necessity of maintenance therapy, or what marker(s) to use to monitor disease activity. Moreover, experience with IgG4-related disease other than AIP is very limited, making worldwide accumulation of such cases and a prospective controlled trial with steroid therapy necessary to establish the optimal treatment strategy.
Keywords: steroid therapy